The Students’ Perceptions of National Examination Washback: A Case Study at MTS Daarul ‘Ulya Metro - Ahmad Madkur; Dedi Irwansyah (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
Studies on washback of testing have been recently conducted. This demonstrates that there is a growing awareness that testing can have consequences beyond just the classroom. For one decade, Ministry of Education in Indonesia has administered National Examination (NE) as the standardized test for passing grade requirement. In spite of its good aim, NE has become one of controversial issues among educators, students and even parents. Some say yes while some others say no. This paper was mainly attempted to display some impacts, not all, of NE toward the test takers, the students. A qualitative research was employed where the data taken from observation and questionnaires to 20 students. The result of the study showed that most of the students felt unconfident with their score in National Examination due to the fact that their English competence was considered low. However, the difficulty of NE did not significantly affect their studying English language. In other words, the washback of NE on their study was negative.